The THE ROLE OF SUBJECTIVE WELL-BEING IN REDUCING TECHNOSTRESS AMONG TELECOMMUNICATION EMPLOYEES IN JAMBI: ROLE OF SUBJECTIVE WELL-BEING IN REDUCING TECHNOSTRESS AMONG TELECOMMUNICATION EMPLOYEES IN JAMBI - Nandini Febriani; Rion Nofrianda; Beny Rahim; Marlita Andhika (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2026)
This was conducted to examine post-transformation work dynamics at PT. X’s Jambi Branch, the transformation that took place increased technology-based work demands in digital work environment, which subsequently triggered the onset of technostress. These conditions manifest ad emotional exhaustion, anxiety, and decreased motivation due to increased digital workloads, which ultimately pose a risk to employees subjective well-being. Therefore, this study aims to analyze the negative relationship between subjective well-being and technostress. The study respondents consisted of employees at PT. X’s Branch Jambi, totalling 59 individuals. The instruments used consisted of a subjective well-being scale based on Diener's (1984) theory developed by Cike et al. (2025), as well as a technostress scale based on the dimensions proposed by Tarafdar et al.'s (2007). The analysis results show a correlation indicating a significant negative correlation between subjective well-being and technostress. This means that the higher an employee’s subjective well-being, the lower their technostress.